2011
DOI: 10.1121/1.3559677
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical comparison of attenuation measurement techniques from backscattered ultrasound echoes

Abstract: Accurate characterization of tissue pathologies using ultrasonic attenuation is strongly dependent on the accuracy of the algorithm that is used to obtain the attenuation coefficient estimates. In this paper, computer simulations were used to compare the accuracy and the precision of the three methods that are commonly used to estimate the local ultrasonic attenuation within a region of interest (ROI) in tissue; namely, the spectral log difference method, the spectral difference method, and the hybrid method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 23 publications
2
72
0
Order By: Relevance
“…Our previous studies simulated the role of ROI size in calculation of attenuation and found that the Spectral Log difference algorithm is less dependent on the homogeneity assumption for the tissue compared to the Spectral difference algorithm, but the Spectral Difference algorithm was more precise when the tissue was homogeneous [39]. In addition, our simulations showed that if the ROI size is small, the attenuation estimates obtained will have higher variance [39]. However, the homogeneity assumption might be better approximated by smaller ROI sizes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous studies simulated the role of ROI size in calculation of attenuation and found that the Spectral Log difference algorithm is less dependent on the homogeneity assumption for the tissue compared to the Spectral difference algorithm, but the Spectral Difference algorithm was more precise when the tissue was homogeneous [39]. In addition, our simulations showed that if the ROI size is small, the attenuation estimates obtained will have higher variance [39]. However, the homogeneity assumption might be better approximated by smaller ROI sizes.…”
Section: Discussionmentioning
confidence: 99%
“…We can rewrite equation The size of the ROI was varied in both the axial and lateral direction. Our previous studies have shown that approximately 15 pulse lengths in the axial direction and 15 pulse lengths in the axial direction and 15 echoes in the lateral direction gave a standard deviation on the order of 25% in the attenuation estimates for simulations, phantom experiments, and in the rat cervix when using the spectral log difference algorithm, while the spectral difference algorithm had a standard deviation of less than 13% for the same ROI size [9,37,39].The pulse length was calculated by taking the auto correlation coefficient of time samples from RF echo lines of the phantom data. Samples with absolute correlation coefficient greater than 0.2 were considered correlated and determined the time pulse length.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations